2007
DOI: 10.1016/j.molimm.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cδ binds TIRAP/Mal to participate in TLR signaling

Abstract: Toll-like receptor (TLR) family members recognize specific molecular patterns within pathogens. Signaling through TLRs results in a proximal event that involves direct binding of adaptor proteins to the receptors. We observed that TIRAP/Mal, an adaptor protein for TLR2 and TLR4, binds protein kinase Cdelta (PKCdelta). TIRAP/Mal GST-fusion protein and a TIRAP/Mal antibody were able to precipitate PKCdelta from rat peritoneal macrophage and THP1 cell lysates. Truncation mutants of TIRAP/Mal showed that the TIR d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…Several DAG-activated enzymes are known to be required for full downstream responses during LPS activation. For example, enzymes from the protein kinase C (PKC) family, such as PKCε and PKCd, can associate with different adaptor proteins that are recruited to TLR4 (32,33). Activation of PKCs requires phosphorylation and enhanced levels of DAG, and the action of these kinases affects TLR4 downstream pathways such as MAPK activation, which ensures full production of inflammatory factors (34).…”
Section: Discussionmentioning
confidence: 99%
“…Several DAG-activated enzymes are known to be required for full downstream responses during LPS activation. For example, enzymes from the protein kinase C (PKC) family, such as PKCε and PKCd, can associate with different adaptor proteins that are recruited to TLR4 (32,33). Activation of PKCs requires phosphorylation and enhanced levels of DAG, and the action of these kinases affects TLR4 downstream pathways such as MAPK activation, which ensures full production of inflammatory factors (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although previously published suppression of Mal phosphorylation by a Btk inhibitor LFM-A13 (55) and the interactions studies shown here suggest Btk as the key kinase responsible for tyrosine phosphorylation of Mal, we cannot rule out the involvement of other kinases. Interestingly, protein kinase C␦ (PKC␦) was also reported to bind Mal within its TIR domain, and PKC␦ depletion from RAW cells suppressed TLR2-and TLR4-induced signaling (62). Thus, the involvement of a multikinase complex (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…MyD88 may activate, via several signaling molecules, the TGF-␤-activated kinase 1 (TAK1), which in turn activates among other things signaling pathways leading to the activation of p42/44 and JNK (43). PKC␦ has been shown recently to bind to a TLR signaling complex, namely TIRAP/Mal, and thus participate in TLR signaling (44). In addition, Kang et al showed a role of the phosphatase calcineurin in regulating TLR-activated pathways (30).…”
Section: Discussionmentioning
confidence: 99%